CHINA IN CENTRAL ASIA - PARAMONOV, Vladimir; STROKOV, Aleksey; STOLPOVSKIY, Oleg (CENTRAL ASIA AND THE CAUCASUS, 2010)
For over a century, or over 130 years to be more exact, Central Asia remained part of the Russian Empire and the Soviet Union which replaced it and was treated by China as such. The sudden disintegration of the Soviet Union into independent states confronted Beijing with the need to deal with several of them in Central Asia, which required a new vector of its foreign policy.The over 20-year-long history of China’s policy in Central Asia can be divided into three periods:1. 1992-1995.2. 1996-2001.3. 2001—the present.At the first stage, in the early 1990s, Beijing took its time to acquire a clear idea about the new reality, establish and then develop diplomatic contacts, build up mutual confidence, create a base of treaties and other legal documents, and address the accumulated security-related problems.At the second stage, the mid- and late 1990s, 2000, and the larger part of 2001 (up to the 9/11 events), Central Asia acquired mechanisms and institutions of multisided cooperation (of which the People’s Republic of China was a part); China was expanding its economic presence in the region.At the third stage, which started on the tragic day of 9/11, China demonstrated inordinate activity and launched an “offensive” along all lines clearly determined to take a tighter grip on the region.